Operation Allied Force: Unintended Consequences of the NATO Bombing on Children's Outcomes - Lara Lebedinski; Giuseppe Migali; Miloš Popović; Suncica Vujic (Institute of Labor Economics (IZA), 2021)
This is the first paper that estimates the causal effect of the NATO's Operation Allied Force in Serbia in 1999, on children who were in the womb during the bombing. We investigate the in utero effect in terms of short-term outcomes, such as birthweight, as well as medium-term outcomes measured by grades of 15-year-old pupils at the end of primary school. Using the birth records of the Serbian Statistical Office, we estimate difference-in-differences models, combined with propensity score matching. We compare the birthweight of children born in the same year (1999) and in the months just before and after the bombing, and children born in the same months of the previous year (1998). We then exploit the data on educational achievement at the end of primary school, provided by the Ministry of Education, to estimate matching models of the effect of the bombing on individual grades. Our findings suggest that children in utero during the bombing were 2pp more likely to be born with a lower than average birthweight. In the medium-term, we find a statistically significant and negative effect (around -1%) of the bombing on maths grades and Serbian language at primary school, and a 1% increase in the probability to enrol on vocational secondary schools. Overall, our results confirm the importance of the negative effects on children in the aftermath of large-scale disasters, and the necessity of policy interventions to mitigate them.
Keywords: I15; J13; O15; 330; human capital formation; children; armed conflict; in-utero effect